2007
DOI: 10.1007/s10526-007-9126-9
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of entomopathogenic hypocrealean fungi infecting Anoplophora glabripennis

Abstract: Table 4 Median survival time (and 95% confidence intervals) and percent of cadavers with fungal outgrowth for A. glabripennis adults treated with suspensions of 10 7 conidia/ml of three Metarhizium anisopliae isolates (Bioassay F) Fungal isolate Number of insects Days to death (ST 50 ± CI) A,B % Fungal outgrowth 2 ARSEF 7234 (VD 1) 63 5.0 (4.0-7.0) a 90.5 a ARSEF 7711 (F 52) 62 6.0 (5.0-6.0) a 77.4 ab ATCC 62176 (ESC 1) 63 6.0 (5.0-7.0) a 61.9 b A Bioassays censored at 15 days B Values followed by the same let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Common entomopathogenic fungi include Beauveria spp., Isaria farinosa (often included in Paecilomyces) and Metarhizium (e.g., Dubois et al 2008;Meyers et al 2009); see also Benham (1971) for a survey of fungi, bacteria and viruses attacking cerambycids. Common entomopathogenic fungi include Beauveria spp., Isaria farinosa (often included in Paecilomyces) and Metarhizium (e.g., Dubois et al 2008;Meyers et al 2009); see also Benham (1971) for a survey of fungi, bacteria and viruses attacking cerambycids.…”
Section: Cerambycidae Latreille 1802mentioning
confidence: 99%
“…Common entomopathogenic fungi include Beauveria spp., Isaria farinosa (often included in Paecilomyces) and Metarhizium (e.g., Dubois et al 2008;Meyers et al 2009); see also Benham (1971) for a survey of fungi, bacteria and viruses attacking cerambycids. Common entomopathogenic fungi include Beauveria spp., Isaria farinosa (often included in Paecilomyces) and Metarhizium (e.g., Dubois et al 2008;Meyers et al 2009); see also Benham (1971) for a survey of fungi, bacteria and viruses attacking cerambycids.…”
Section: Cerambycidae Latreille 1802mentioning
confidence: 99%
“…Five species of fungi were found that are pathogenic to Anoplophora spp., of which three species Beauveria bassiana (Balsamo) Vuillemin (Hypocreales: Cordycipitaceae), Beauveria brongniartii (Saccardo) Petch (Hypocreales: Cordycipitaceae) and Metarhizium brunneum Petch (formally M. anisopliae ) (Hypocreales: Clavicipitaceae) can infect both A. chinensis and A. glabripennis . Two strains of Isaria farinosa (Holmskiold) Fries (Hypocreales: Clavicipitaceae) and the microsporidium Nosema glabripennis Zhang (Dissociodihaplophasida: Nosematidae) have been shown to infect A. glabripennis . Differences in experimental design make it difficult to compare the pathogenicity of these species in terms of mortality rate and lifespan of infected beetles, but several studies on A. glabripennis have compared the effectiveness of multiple species and found that M. brunneum and B. brongniartii were the most pathogenic .…”
Section: Entomopathogenic Fungimentioning
confidence: 99%
“…Two strains of Isaria farinosa (Holmskiold) Fries (Hypocreales: Clavicipitaceae) and the microsporidium Nosema glabripennis Zhang (Dissociodihaplophasida: Nosematidae) have been shown to infect A. glabripennis . Differences in experimental design make it difficult to compare the pathogenicity of these species in terms of mortality rate and lifespan of infected beetles, but several studies on A. glabripennis have compared the effectiveness of multiple species and found that M. brunneum and B. brongniartii were the most pathogenic . Isaria farinosa and N. glabripennis both have significantly lower mortality rates than other fungal species, so may not be effective as control agents .…”
Section: Entomopathogenic Fungimentioning
confidence: 99%
“…Additionally, the use of fabric bands impregnated with entomopathogenic fungi (e.g. Metarhizum anisopliae ) and possible use of entomopathogenic nematodes have been investigated . However, to date, there have been no biological controls deployed operationally against ALB in North America.…”
Section: Introductionmentioning
confidence: 99%